Managing hazardous air pollutants : state of the art - Chow, Winston; Connor, Katherine K.; International Conference on Managing Hazardous Air Pollutant : State of the Art (1st : 1991 : Washington, DC) (Boca Raton, FL : Lewis Publishers, 1993)
10